2011
DOI: 10.1021/cs1000976
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthetic Strategy of Mesoporous ZSM-5 Zeolites by Using Conventional Block Copolymer Templates and the Improved Catalytic Properties

Abstract: Employing conventional block copolymers as scaffold, a direct synthetic route of mesoporous zeolites has been developed with the assistance of post-steaming treatment. Such hierarchical micro/mesostructure demonstrated the greatly enhanced catalytic activity for probe reactions, such as cracking of triisopropylbenzene and esterification reactions involving bulky molecules, because of the increased external surface, and the diminished coke formation by the greatly shortened diffusion length in microporous netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(108 citation statements)
references
References 38 publications
3
103
0
2
Order By: Relevance
“…The bands at 550 cm -1 and 980 cm -1 in the spectra , and AAM [20] showed that Hie-AMS samples are hierarchical porous aluminosilicates. The N2 adsorption-desorption isotherm of the microporous ZSM-5 possesses a typical type I according to the IUPAC classification [24], as shown in Fig. 3.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands at 550 cm -1 and 980 cm -1 in the spectra , and AAM [20] showed that Hie-AMS samples are hierarchical porous aluminosilicates. The N2 adsorption-desorption isotherm of the microporous ZSM-5 possesses a typical type I according to the IUPAC classification [24], as shown in Fig. 3.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
“…The hysteresis loop of Hie-AMS at relatively high pressure (0.85-0.95) is assigned to H4 hysteresis loop. Materials containing both microporous and mesoporous generally have H4 hysteresis loops [24]. Correspondingly, the sample mesoporous size distribution is estimated at about 3-6 nm by applying a BJH method (Fig.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
“…4 In recent years, several promising strategies have been developed to solve the diffusion limitation problems, the synthesis of hierarchical zeolites with both mesoporosity and microporosity is considered to be one of the most promising methods due to the significantly reduced diffusion length. It was mainly divided into two routes: non-templating method and templating method [10]. Dealumination and desilication of pre-synthesized zeolite crystals, as a non-templating method, has a great potential for commercialization due to the relatively simple process.…”
Section: Introductionmentioning
confidence: 99%
“…The resistancet od eactivation in the aerobic oxidation may be attributedt ot he improved mass transport ability of guest species through the interconnected mesoporousn etwork. [40,41] The conversion decrease to 81 %a st he catalyst is reused fort he fifth time. The SEM image of the Cu 3 (BTC) 2 after being used for five runs shows that some of mesopores of the MOF are partially blocked( Figure S10).…”
Section: àmentioning
confidence: 99%